Catalytic Oxidative Desulfurization of 4-Methyldibenzothiophene by Ni/Al Modified Titanium Dioxide and Zinc Oxide - Risfidian Mohadi; Neza Rahayu Palapa; Sahrul Wibiyan; Mardiyanto; Rohmatullaili; Erni Salasia Fitri; Aldes Lesbani (Science and Technology Indonesia, 2023)
In this study, composite layer double hydroxide-metal oxide catalysts (Ni/Al-TiO2 and Ni/Al-ZnO) were successfully prepared and utilized for the oxidative desulfurization of dibenzothiophene. The catalysts were characterized using XRD, FTIR, and SEM-EDS analysis. The diffraction patterns confirmed the successful synthesis of the composite materials, while the FTIR spectra exhibited absorption bands at specific wavenumbers 3480 cm-1, 1630 cm-1, 1376 cm-1, 830 cm-1, 775 cm-1, and 683 cm-1. The surface morphology of the catalysts showed variations, with Ni/Al-LDH having a smooth particle surface and long particle shape, while Ni/Al-ZnO and Ni/Al-TiO2 formed grain-like or aggregated structures. EDS analysis confirmed the presence of Ni/Al, Ti, and Zn elements in the composites, with Ti and Zn accounting for 29.3% and 10.7% of the composite mass, respectively. The optimized reaction conditions included a reaction time of 40 minutes, catalyst dosage of 0.25 g, temperature of 50°C, and the use of n-hexane as the solvent. The catalysts demonstrated a heterogeneous nature and proved to be reusable, as the conversion of dibenzothiophene remained above 90% even after three catalytic reactions, with Ni/Al-TiO2 and Ni/Al-ZnO composites maintaining conversion rates of 99.36% and 99.32%, respectively.